Breastfeeding Protection, Promotion, and Support in Humanitarian Emergencies: A Systematic Review of Literature. (November 2020) - Dall'Oglio, Immacolata; Marchetti, Francesca; Mascolo, Rachele; Amadio, Patrizia; Gawronski, Orsola; Clemente, Maria; Dotta, Andrea; Ferro, Federico; Garofalo, Antonio; Salvatori, Guglielmo; Tarantino, Antonella; Tiozzo, Emanuela; et al.
Background: Infants, young children, and their mothers are vulnerable in humanitarian emergencies. The health benefits of optimal breastfeeding practices in emergency settings have been demonstrated by many researchers. Infant and Young Children Feeding in Emergency guidelines illustrate a series of interventions to protect, promote, and support breastfeeding, but unfortunately, these recommendations are still scarcely applied. Research Aims: (1) To review the literature describing the effectiveness of breastfeeding protection, promotion, and support interventions in humanitarian emergency contexts; (2) to describe the influence of interventions on breastfeeding initiation, exclusivity, and duration; and (3) to evaluate relevant mother and infant/child outcomes available in the literature. Methods: PubMed, CINAHL, Cochrane Library, Psychology Database, JSTOR, Web of Science, EMBASE, and Ovid were searched for articles that examined breastfeeding protection, promotion, or support interventions and the resulting outcomes without any time limits ( N = 10). Articles that did not include the interventions and related outcomes were excluded ( n = 1, 391). Results: Improved breastfeeding outcomes were reported in four (40%) papers, and three (30%) highlighted a behavioral change in infant and young child feeding practices following the implementation of the interventions. Increased knowledge about appropriate infant and young child feeding practices among mothers and humanitarian/health staff was reported in eight (80%) papers. However, outcomes were sometimes only generically reported, and some of the included papers had a low strength of evidence. Conclusion: In the literature, there is a great dearth of studies evaluating the influence of interventions aimed at improving breastfeeding in emergency settings. More evidence is urgently needed to encourage and implement optimal breastfeeding practices.